Evaluation of survival rate of implants with immediate loading compared to implants with conventional load in implants with fixed prosthesis, update of a systematic review and meta-analysis - Meysam Heidari; Masomeh Rostamzadeh; Ideh Talimkhani (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: Edentulism is described as "ultimate indicator of disease burden for oral health" that affects quality of life. The most common treating method is an implant, which has a favorable survival rate for replacing lost teeth and improving the quality of life. The aim of this study is to review the rate of bone resorption, success rate and gingivitis in implants with immediate loading (IL) compared to conventional Lading (CL), which was performed as an update of the meta-analysis study by Chen J, et al (2019). Materials and Methods: The study is a systematic review and meta-analysis, using a descriptive-analytical method and in four stages. The desired effect size included survival risk ratio and mean difference, crestal bone surface and probing depth in the group using CL implants compared to IL implants. For meta-analysis, the risk ratio, logarithm and standard deviation of the logarithm were combined using the fixed effect model. To calculate the mean difference, the weighted mean difference index was used and they were combined and compared using the fixed effect model. Cochran's Q and I2 tests were used to examine heterogeneity and variance between selected studies; Egger's test was used to evaluate publication bias. All these analyzes were done with STATA-17. Results: After searching the desired databases, 2089 articles were retrieved; After removing the duplicates in the Endnote-X9, 1088 articles entered the screening step based on the title, and finally 61 articles with the inclusion criteria were included in the study, that 11 new studies were added. Conclusion: In general, the survival rate and the average crestal bone level in the IL implants compared to the CL implants were higher by 0.78 and 0.32, respectively, and the weighted average probing depth was lower by 0.25.